Women’s decision-making, child nutrition and motherhood: evidence from South Africa - Adediran, Olanrewaju Adewole (University of the Witwatersrand, Johannesburg, 2021)
The thesis comprised three main essays. These are issues affecting the degree of equality in economic opportunities and the dynamics of earnings inequalities within the labour market. The inferences made about women's decision-making and their varied labour income due to the number of children given birth in South Africa. First, much of the existing literature contends that income is a key determinant of household decision-making. Yet the causal connection between income and household decision-making is difficult to ascertain, given the obvious endogeneity bias that may arise from reverse causality and omitting (unobserved) confounding variables correlated with income and the household decision- making measures. Thus, this study exploited the exogenous variation in household income and their decision-making. This is based on a unique natural experiment in South Africa using age discontinuity in eligibility for Old Age Pension (OAP) income transfer- to identify the causal effect of income on household decision-making. Using a regression discontinuity design (RDD), the study found that women's decision-making responded to changes in income from OAP transfer more than that of men. More so, the OAP transfer influenced women decision-making by 12% points for the recipient more than non-recipient. The results from the quantile treatment effect confirmed that the OAP income transfer effect is heterogeneous across the distribution of household decision-making. The study suggested that women should be used as a channel of distribution of social grant (in development programmes) to reduced inequality and achieve gender equality
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the Degree of Doctor of Philosophy in Economics, University of the Witwatersrand, Johannesburg, 2021
Keywords: Household decision-making; Old Age Pension (OAP) transfer; Women’s decision-making; Child Nutritional outcomes; Number of children; Mother’s labour income; Control Function Approach; UCTD; SDG-5: Gender equality